2013
DOI: 10.1177/1403494813493151
|View full text |Cite
|
Sign up to set email alerts
|

Recent temporal trends in sleep duration, domain-specific sedentary behaviour and physical activity. A survey among 25–79-year-old Danish adults

Abstract: Adult Danish men and women spend an increased amount of time sitting down at work and during leisure time, but also on leisure time MVPA. As duration of sleep is unaltered findings suggest that low intensity physical activity may be displaced in everyday life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 30 publications
(36 reference statements)
1
42
0
3
Order By: Relevance
“…This goes beyond existing work that has focused on watching TV . To our knowledge, only one study has looked at possible associations between sleep duration and time spent sitting at work or sitting during leisure time, but found no such associations .…”
Section: Introductionmentioning
confidence: 83%
“…This goes beyond existing work that has focused on watching TV . To our knowledge, only one study has looked at possible associations between sleep duration and time spent sitting at work or sitting during leisure time, but found no such associations .…”
Section: Introductionmentioning
confidence: 83%
“…5 METs while in a sitting or reclining position [11], constitutes a distinct and independent risk factor for cardiometabolic morbidities [12]. Thus, recent population-based studies have shown an increase in sitting time during leisure time, irrespective of an increased level of physical activity [13,14], indicating a need to measure both physical activity and sitting time in relation to health profile.…”
Section: Introductionmentioning
confidence: 99%
“…In developed countries, adult populations spend most of their waking time engaged in sedentary behaviours 2 3. Sedentary behaviours encompass sitting at work, watching television, using a computer, and driving a car, but are distinctively different behaviours to a lack of moderate-to-vigorous physical activity, as it is possible to sit for prolonged periods, and also meet the recommendations for leisure time moderate-to-vigorous physical activity.…”
Section: Introductionmentioning
confidence: 99%